If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5Z + -8Z = 12 Combine like terms: 5Z + -8Z = -3Z -3Z = 12 Solving -3Z = 12 Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Divide each side by '-3'. Z = -4 Simplifying Z = -4
| -5x=16.5 | | 3[2x+1]+x=-39 | | 2-4a-6=-8 | | 6z-7=13 | | 2-4a-6=8 | | 3=6p^2-7p | | 7x+1-4=-16 | | 2e-11=7e+8 | | -2-4(m-4)=24 | | 7x+1-4=16 | | -3x^3+15x^2+42=0 | | X-8.65=-9.13 | | 2+4(5+m)=60 | | 2x-1+5=-14 | | -x^2-14x-45=0 | | y+8=9 | | x^2-10x+30=0 | | 3x+11=5x+3-4x+1 | | 2y+24=28 | | -x^2-14x-48=0 | | 6p-3p=14+6 | | 3x^2+36x+81=0 | | 2x*2y=8 | | 3z+10=25 | | x^3+3x^2-40x=0 | | 3a+36=5a | | y+20=22 | | 2y+13=21 | | 5x-4+7=8-2 | | 5x-4+7=8-2 | | 4y+18=26 | | x^2-(x+25)=(x-2) |